Knowledge, Attitudes and Practices (Kap) Regarding Early Childhood Caries among Nurses Working in a Low Socio-Economic Area - Nadia Mohamed; Jo Barnes (Archives of Community Medicine and Public Health - Peertechz Publications, 2015)
Early Childhood Caries (ECC) has been recognized by the American Academy of Pediatric Dentistry [1] as a "significant public health problem" and it still affects a large number of children worldwide [2,3]. Dye et al. [3], stated that dental caries is "the most common chronic disease of childhood in the United States". Even though caries in itself is not life-threatening, the extent of this oral health problem is of major significance as it ultimately has an impact on general health and well-being and affects the quality of life. Untreated dental caries can lead to abscess formation and the resultant pain can influence the ability of children to function optimally in their day to day lives [4]. Decay of the primary dentition is also one of the main reasons why children are hospitalized [2]. These children are often under the age of 5 years, cooperation is usually poor. This means that more expensive treatment options such as general anesthesia or sedation have to be considered in most cases [4,5].